KOMODIFIKASI OBJEK DIFABEL DALAM MEDIA ONLINE TEMPO.CO - Syena Meuthia, (2022)
Problem of stigma and discrimination faced by people with disabilities today does not only occur in people's lives, but is perpetuated by online media in their reporting. This study aims to interpret the critical discourse on disability in one of the online media, is Tempo.co. By using the discourse analysis model of Teun A. Van Dijk in critical discourse analysis (AWK) to find the commodification of disabled objects in the Tempo.co online diffable rubric as well as the ideology behind Tempo.co's media in discussing disabled objects. The method used is descriptive qualitative by using data sources in the form of documents with a total of 12 news on the Tempo.co website, each 4 news editions of Accessibility, 5 news editions of Inclusivity, and 3 editions of Rehabilitation. Sampling technique is done by triangulation of data. Researchers gather sample of news from October to November 2022 with the unit of analysis of text structure, social cognition, and social analysis. The results of this study show that there is an alignment of the media with disabilities. In the discourse developed in the Tempo.co diffable rubric, the discourse on disability becomes a selling point through the commodification of content. In addition, the use of language as an instrument of media power is seen by discussing disability using humanist language without stigma and discrimination to disabled.